Galectins as checkpoints of the immune system in cancers, their clinical relevance, and implication in clinical trials - Compagno, Daniel Georges (2020)
Galectins are small proteins with pleiotropic functions, which depend on both their lectin (glycan recognition) and non-lectin (recognition of other biomolecules besides glycans) interactions. Currently, 15 members of this family have been described in mammals, each with its structural and ligand recognition particularities. The galectin/ligand interaction translates into a plethora of biological functions that are particular for each cell/tissue type. In this sense, the cells of the immune system are highly sensitive to the action of these small and essential proteins. While galectins play central roles in tumor progression, they are also excellent negative regulators (checkpoints) of the immune cell functions, participating in the creation of a microenvironment that promotes tumor escape. This review aims to give an updated view on how galectins control the tumor’s immune attack depending on the tumor microenvironment, because determining which galectins are essential and the role they play will help to develop future clinical trials and benefit patients with incurable cancer.